Antimicrobial and other beneficial properties of fodder species with potential use in controlling diarrhoeagenic Escherichia coli in cattle - McGaw, Lyndy Joy (University of Pretoria, 2024)
Thesis (PhD (Paraclinical Sciences))--University of Pretoria, 2023.